Knowledge Relation of Pregnant Women About Pregnancy Danger Signs with Antenatal Care Visits in Work Area of Hamparan-Perak’s Public Health Center - Dwi Pratiwi Kasmara (Poltekkes Kemenkes Pangkalpinang, 2022)
Background: Maternal Mortality Rate (MMR) is one indicator that can describe the welfare of society in a country. According to data from the World Health Organization (WHO), maternal mortality in Indonesia in 2013 was still dominated by three main causes of death, namely bleeding by 30.13%, hypertension in pregnancy by 27.1%, and infection by 7.3%. one of the causes of maternal mortality in Indonesia whose incidence continues to increase, namely 1% in 2010 1.1% in 2011 and 1.8% in 2012. In monitoring the health service program for pregnant women, it can be assessed using the coverage indicators K1 and K4.Objective: The purpose of this study was to determine the knowledge relation of Pregnant Women about the danger signs of pregnancy with Antenatal Care (ANC) visits.Method: This research is an analytic study with a cross-sectional approach using primary and secondary data, primary data using a questionnaire with 20 questions. The sample used is 65 people, the sampling method is by accidental sampling techniqueResult: There is a relationship between knowledge of pregnant women about danger signs of pregnancy with antenatal care (ANC) visits where (X² count = 64.75) > X² table (3.481) at Hamparan-Perak’s public Health Center in 2021Conclusion: There is a relationship between knowledge of pregnant women about danger signs of pregnancy with ANC visits at Hamparan-Perak’s public Health Center in 2021 Keywords: Knowledge; Pregnant Women; Danger Signs of Pregnancy; ANC Visits